Diagnosis and treatment of migraine: an analysis of the latest diagnostic and therapeutic guidelines - Joanna Cieszkowska; Karina Otręba; Karolina Czupryńska; Piotr Daniel; Michał Leśkiewicz; Justyna Aleksandra Składanek (Kazimierz Wielki University, 2024)
Introduction Migraine is a common disease that a large part of the population struggles with. Stressful work and poor eating habits increase the risk of headaches. The basic therapy is lifestyle change, and when this does not bring results, medications are used. The choice of the appropriate preparation depends on the characteristics of the pain and the patient's condition. Knowledge about different treatment methods can improve patients' lives. Aim of the study The aim of the article was to present current guidelines for migraine therapy depending on the individual patient's requirements. Materials and methods The article is the result of a review of recent scientific literature using PubMed, Scopus and Google Scholar databases. The literature was reviewed using the keywords. Results Many clinical trials have examined the effects of different classes of drugs on migraine headaches. The final effect depends on the dose used, the moment of drug administration, and the patient's age, gender and health condition. Doctors often have to modify therapy within the same group of drugs to find a drug that will work for a given patient. Conclusions Clinical trials have proven the effectiveness of, among others, non-steroidal anti-inflammatory drugs, triptans and botulinum neurotoxin. A clinically significant analgesic effect is sometimes characterized by side effects, therefore careful selection of the preparation and patient observation are important.